Pigmented Villonodular Synovitis: A Comprehensive Review and Proposed Treatment Algorithm. Issue 7 (19th July 2016) - Stephan, Stephen R.; Shallop, Brandon; Lackman, Richard; Kim, Tae Won B.; Mulcahey, Mary K.
Abstract : Evidence now exists suggesting a neoplastic origin for pigmented villonodular synovitis, including a thorough description of the translocations involved. Arthroscopic excision for localized pigmented villonodular synovitis allows for both minimal recurrence and morbidity when compared with open excision; however, open excision still plays an important role in treating posterior compartment nodules. The optimal surgical treatment for diffuse pigmented villonodular synovitis is still a matter for debate, with combined anterior arthroscopic and open posterior excision being considered the preferred method. Radiation therapy has re-emerged as an additional treatment method for pigmented villonodular synovitis; however, the potential for serious toxicity makes it a questionable option, especially for such a benign condition. Small molecule and monoclonal antibody targeted therapies are being investigated as novel treatment methods for pigmented villonodular synovitis, with promising results.